Voice Visibility and Dignity : Towards a right-based framework for migrant workers (Thiruvananthapuram Vakkom Moulavi Foundation Trust (VMFT), 2020)
Report of the round-table discussion- Inter-state migrants: Kerala's Experience during COVID-19 and Directions for the Future
Keywords: Experience of migrant workers in Kerala during Covid-19 pandemic -- migrant workers in Kerala -- Kerala's approach to migrant workers, Holistic approach to ensuring the welfare of migrant workers, History of labour activism and role of societal norms : unique case of Kerala -- Role of police in Relief efforts -- Improving welfare and opportunities for migrants, Role of media in covering migrant issues,Strengthening public policy and programmes, Kerala economy